Gastroenterological and immunological aspects of cow's milk protein sensitive enteropathy - P. D. Manuel (Paediatrica Indonesiana, 1981)
CMPI is a 20th century disease. Until fairly recently it was not possible to feed safely large numbers of young infants other than by human breast milk. In our time, however, cow's milk protein is quantitatively the most important dietary protein in young infants.